2021
DOI: 10.3390/ph14100980
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic Acid Inhibits Coronavirus Strain 229E Infection of Human Epithelial Lung Cells

Abstract: Since December 2019, the COVID-19 pandemic has affected more than 200 million individuals around the globe and caused millions of deaths. Although there are now multiple vaccines for SARS-CoV-2, their efficacy may be limited by current and future viral mutations. Therefore, effective antiviral compounds are an essential component to win the battle against the family of coronaviruses. Ginkgolic Acid (GA) is a pan-antiviral molecule with proven effective in vitro and in vivo activity. We previously demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Lyu et al summarized and discussed the clinical effects and potential mechanisms of TCM at different disease stages for the treatment of COVID-19, emphasizing the scientific value of TCM in combating COVID-19 [12] . Ginkgolic acid, the main component of Ginkgo biloba , has a variety of biological activities, such as antitumor [13] , anti-inflammatory [14] , antibacterial [15] , and broad-spectrum antiviral effects [16] , [17] , [18] . A recent study found that Ginkgolic acid C15:1 (GA151) inhibited several enzymes that play crucial roles in viral polyprotein processing, e.g., 3-chymotrypsin-like protease (3CL pro ) and papain-like protease (PL pro ) [19] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lyu et al summarized and discussed the clinical effects and potential mechanisms of TCM at different disease stages for the treatment of COVID-19, emphasizing the scientific value of TCM in combating COVID-19 [12] . Ginkgolic acid, the main component of Ginkgo biloba , has a variety of biological activities, such as antitumor [13] , anti-inflammatory [14] , antibacterial [15] , and broad-spectrum antiviral effects [16] , [17] , [18] . A recent study found that Ginkgolic acid C15:1 (GA151) inhibited several enzymes that play crucial roles in viral polyprotein processing, e.g., 3-chymotrypsin-like protease (3CL pro ) and papain-like protease (PL pro ) [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GA151 exhibited a broad-spectrum inhibitory effect on the viral fusion process of several enveloped viruses, such as Herpes Simplex Virus 1 (HSV-1), Human Cytomegalovirus (HCMV), and Zika Virus (ZIKV) [21] . Furthermore, GA151 can inhibit both the production of human coronavirus and the synthesis of viral N protein, which is conserved among the α, β, and γ genera of coronaviruses [18] . Therefore, further study on the antiviral mechanism of Ginkgolic acid is of great significance in exploring effective compounds against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the mechanism, the biological activity of AEG12 is dependent on their bound hydrophobic ligands, with the protein itself acting primarily as a delivery vehicle. Indeed, the greatest enhancement in the therapeutic index was observed in GA‐AEG12: a ligand whose ability to inhibit viral membrane fusion and infectivity has been previously documented [14,15,24]. However, these studies found that free GA interacted with serum factors such as albumins and other lipid‐binding proteins, reducing its efficacy in a therapeutic setting [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies described techniques through which lipid-binding proteins could be stripped of their endogenous cargoes, and quantitatively re-loaded with a defined set of hydrophobic ligands [12]. Using this technique, we prepared samples of AEG12 loaded with docosanol (Doc), 16:0-lysophosphatidylcholine (LPC) and GA: compounds that have been previously characterized in the literature as hydrophobic viral inhibitors [14][15][16][17]24,25]. Binding of all three inhibitors resulted in a notable increase in the thermostability of AEG12 relative to the Apo control, with melting temperatures (MT AEG12 ) comparable to those observed for AEG12 bound to its natural nMix ligands (Fig.…”
Section: Aeg12 Binds and Delivers Hydrophobic Fusion Inhibitors Into ...mentioning
confidence: 99%
“…[ 61 ] Broad‐spectrum antiviral activity and its potential role in COVID‐19 management of GA should be emphasized as well. Bhutta et al [ 62 ] have demonstrated that this phytochemical significantly protected against human coronavirus strain 229E (HCoV‐229E) infection in human epithelial lung cells (MRC‐5) by restricting progeny virus production, viral protein expression, and cytopathic effects. Significantly, the anti‐inflammatory activity of quercetin through stabilization of mast cells, modulation of dendritic cells activity, and inhibition of proinflammatory cytokines release from activated macrophages in the lung has also been reported.…”
Section: G Biloba and Covid‐19mentioning
confidence: 99%